2014
DOI: 10.1007/s12011-014-0056-y
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Selenium and Polysaccharide of Atractylodes macrocephala Koidz. (PAMK) on Immune Response in Chicken Spleen Under Heat Stress

Abstract: The aim of the present study was to investigate the effect of selenium (Se), polysaccharide of Atractylodes macrocephala Koidz. (PAMK), and the combination of Se and PAMK on the immune response, heat shock protein (HSP) levels under heat stress (HS) condition in chicken spleen. Two hundred chickens were randomly divided into two groups, the HS group and the control (Con) group. Then these chickens were treated with Se (0.3 mg/kg), PAMK (200 mg/kg) alone, and the combination of Se (0.3 mg/kg) and PAMK (200 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 31 publications
6
42
0
Order By: Relevance
“…For example, heat stress in black-boned chickens reduced daily feed intake and BW gain; decreased serum GSH and inhibited GSH-Px, SOD and CAT activities compared with birds subjected to thermo-neutral circumstances [122]. Similarly, in chickens heat stress induced higher levels of TNF-α, IL-4, HSP27, HSP70, and MDA levels but lower level of IFN-γ, IL-2, GSH-Px, and SOD in spleen [123][124]. These responses were ameliorated by the…”
Section: Heat Stressmentioning
confidence: 99%
“…For example, heat stress in black-boned chickens reduced daily feed intake and BW gain; decreased serum GSH and inhibited GSH-Px, SOD and CAT activities compared with birds subjected to thermo-neutral circumstances [122]. Similarly, in chickens heat stress induced higher levels of TNF-α, IL-4, HSP27, HSP70, and MDA levels but lower level of IFN-γ, IL-2, GSH-Px, and SOD in spleen [123][124]. These responses were ameliorated by the…”
Section: Heat Stressmentioning
confidence: 99%
“…Data are the means±SD, n=5. Bars without a common letter were significantly different (P<0.05) our prior study [4], we showed that chronic HS increased the levels of TNF-α and IL-4 but decreased the levels of IFN-γ and IL-2 in the chicken spleen [11]. In the present study, we exposed chickens to 1 week of acute HS and examined the effect of HS on the chicken immune system.…”
Section: Discussionmentioning
confidence: 48%
“…In our prior study, we found that chronic HS influenced the levels of cytokines and induced oxidative injuries in chicken spleens [11]. Compared with chronic HS, acute HS was also detrimental to the immune system.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…[6][7][8][9][10][11] Recent research also revealed that another important biological effect of PAMK is to resist heat stress and maintain the immune function at a stable level. 5,12,13 However, there has been no report about the effects of PAMK on alleviating immunosuppression.…”
Section: Introductionmentioning
confidence: 99%